Teaching health in an era of inequality. (2018) - Buder, Iris; Jennings, Jake
With rising inequalities in the USA health disparities are also increasing, which is especially pronounced when viewed by racial/ethnic group and by socio-economic status. This paper provides an outline for instructing on these disparities, and specifically their impact on health outcomes.